2010
DOI: 10.3311/pp.ci.2010-2.02
|View full text |Cite
|
Sign up to set email alerts
|

Combined shear and patch loading of girders with corrugated webs

Abstract: The corrugated steel plate has been increasingly used as web of steel and composite bridges. When such a bridge is incrementally launched, the web panels are often subjected to combined shear and patch loading. There are only a few investigations available in the literature which are dealing with this interaction type, therefore the current research of the authors focuses on the analysis of the combined shear and patch loading in case of corrugated web girders. Based on patch loading tests executed on 12 short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In the ANSYS [15] finite element software environment a 4-node shell element (SHELL 181) is applied, which can model thin and moderately thick plated structures and it is well-suited for large strain nonlinear applications. Note that this finite element was applied in Liu's numerical study [12] of non-corroded angle elements under compression and by Kövesdi et al [16] to investigate stability problems of steel girders with trapezoidal webs. In case of shell models the different continuously rough surface cannot be modelled accurately if the corrosion is different on the two sides of the legs.…”
Section: Corrosion Modellingmentioning
confidence: 99%
“…In the ANSYS [15] finite element software environment a 4-node shell element (SHELL 181) is applied, which can model thin and moderately thick plated structures and it is well-suited for large strain nonlinear applications. Note that this finite element was applied in Liu's numerical study [12] of non-corroded angle elements under compression and by Kövesdi et al [16] to investigate stability problems of steel girders with trapezoidal webs. In case of shell models the different continuously rough surface cannot be modelled accurately if the corrosion is different on the two sides of the legs.…”
Section: Corrosion Modellingmentioning
confidence: 99%
“…For instance, Pasternak and Kubieniec [8] concluded that the buckling resistance of typical sinusoidal corrugated web girders with a web thickness of 1.5 to 3 mm are comparable with conventional girders manufactured with 12 mm thick flat webs. Recently, a number of experiments dealing with the particular behaviour of this girder type have been carried out at room temperature [9][10][11][12]; in addition, Annex D of EN 1993-1-5 [13] deals with design rules for girders with corrugated webs at room temperatures. On the other hand, structural behaviour of corrugated web girders at elevated temperature has not been widely analysed [14][15][16] and requires further investigation and clarification.…”
Section: Introductionmentioning
confidence: 99%